Pemanfaatan Bioplastik Timbal untuk Menurunkan Dosis Radiasi pada Pemeriksaan Femur dengan Posisi Detektor Potret dan Diagonal melalui Pendekatan Citra dan Anatomi: RADIATION DOSE REDUCTION IN FEMUR EXAMINATION USING LEAD BIOPLASTICS: AN IMAGING AND ANATOMICAL APPROACH - Alvin Fachrully Septiano; Oktarina Damayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
X-ray radiation in the medical field offers substantial diagnostic benefits but also poses potential risks to both patients and medical personnel. This study aims to evaluate the effectiveness of bioplastic made from cassava starch and lead acetate as a radiation dose absorber in femur radiographic examinations. The examinations were conducted using Anteroposterior (AP) and Lateral projections with portrait and diagonal detector positions. Image processing utilized the Gaussian High Pass Filter (GHPF) method with cut-off frequencies of 5, 10, and 15 Hz. Image analysis was performed using Contrast to Noise Ratio (CNR) and Peak Signal to Noise Ratio (PSNR). The results indicated that the use of bioplastic reduced CNR and PSNR values compared to examinations without bioplastic, although the image quality remained within acceptable clinical limits. For instance, in the AP diagonal projection with a 5 Hz cut-off, the CNR value for the proximal femur was 22.86 (with bioplastic) versus 21.95 (without bioplastic), while the corresponding PSNR values were 11.1 and 11.6, respectively. Additionally, radiation dose attenuation was supported by increased Mean Squared Error (MSE) values, indicating effective shielding by the bioplastic. Cut-off frequencies of 5 and 10 yielded the best image quality in both conditions.